Diminished reactivity effect of confidence rating on perceptual decision-making in depression - Zhang, Luoya; Liu, Yelu; Wang, Yuxiang; Gong, Ke; Liu, Kezhi; Lei, Wei; Chen, Jing (Frontiers in Neuroscience, 2025)
IntroductionRetrospective confidence ratings (CRs) after decision-making reactively lead to prolonged response times (RTs) and improved decision accuracy, a phenomenon known as the reactivity effect. This effect reflects an individual’s metacognitive control processes. Little is known if depressive pathologies modify the reactivity effect in patients with Major Depressive Disorder (MDD).MethodsThis study investigated the differences in the reactivity effect between 94 patients with MDD and 97 healthy controls (HCs), using a perceptual decision-making task and the Drift Diffusion Model (DDM) analysis.Results and discussionThe results demonstrated that prompted CRs significantly prolonged RTs in both groups. However, prompted CRs improved decision accuracy in HCs, this effect was absent in the MDD group. DDM analysis revealed increased decision thresholds under CR conditions for both groups. Crucially, a significant group×condition interaction emerged for drift rate (v), with HCs demonstrating enhanced evidence accumulation speed compared to MDD patients. These findings indicate impaired metacognitive reactivity effects in MDD through confidence monitoring, highlighting deficits in metacognitive monitoring and control processes associated with depression.